2015
DOI: 10.1080/15324982.2015.1073194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water deficit on growth, nodulation and physiological and biochemical processes inMedicago sativa-rhizobia symbiotic association

Abstract: The effects of water deficit on growth, nodulation, and several physiological and biochemical processes in six symbiotic combinations involving three Moroccan alfalfa (Medicago sativa L.) populations (Tafilalet1, Adis-Tata and Demnate2), an American Moapa variety andtwo rhizobial strains (RhL9 and RhL10) were studied. The experiment was conducted under greenhouse conditions. Seedlings were separately inoculated with the suspension of two rhizobial strains and grown under two irrigation regimes: 80

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 39 publications
6
28
0
1
Order By: Relevance
“…The results of our study showed a signiicant increase of this parameter under water deicit in all the studied symbiotic combinations. However, this increase was not signiicant for the more tolerant combination Ad-RcRh09 which proves the importance of this parameter in the osmotic stress tolerance [24]. The same results have been reported in Refs.…”
Section: Efect On Alfalfa Plant In Symbiosissupporting
confidence: 76%
See 2 more Smart Citations
“…The results of our study showed a signiicant increase of this parameter under water deicit in all the studied symbiotic combinations. However, this increase was not signiicant for the more tolerant combination Ad-RcRh09 which proves the importance of this parameter in the osmotic stress tolerance [24]. The same results have been reported in Refs.…”
Section: Efect On Alfalfa Plant In Symbiosissupporting
confidence: 76%
“…[24], it has been reported that no signiicant correlation was observed between leaf area and relative water content (RWC) and between g s and RWC, while leaf area was found to be highly correlated (r 2 = 0.674) at g s . Thus, we suggest that this could have positive indirect efects on RWC by controlling stomata behaviour, maintaining the leaf area and facilitating water uptake in the event of water deicit [60].…”
Section: Efect On Alfalfa Plant In Symbiosismentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient seed germination, rapid and uniform seedlings emergence lead to successful culture establishment (Chen and Arora, 2011). The Moroccan alfalfa populations are considered as moderately tolerant to drought and salinity but there is a variant behavior within a lot of them (Bouizgaren, 2007;Latrach et al, 2014;Mouradi et al, 2016). In addition, many species and sub-species of Medicago also exhibit traits of agronomic interest, such as tolerance to grazing (rooting ability and regrowth) and disease (Bouizgaren, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have not found any changes in the first days of salt stress [11], while other reported significant decreases in the F v /F m under severe salinity and drought [24]. Mouradi et al, [14] and Fghire et al, [15] proved the efficiency of this tool for determining more drought tolerant genotypes of alfalfa and quinoa respectively. As well as drought, PSII performance decreased under salinity reflected by the decrease in the F v /F m ratio [12].…”
Section: Discussionmentioning
confidence: 99%